2017
DOI: 10.1371/journal.pgen.1006879
|View full text |Cite
|
Sign up to set email alerts
|

Open chromatin profiling identifies AP1 as a transcriptional regulator in oesophageal adenocarcinoma

Abstract: Oesophageal adenocarcinoma (OAC) is one of the ten most prevalent forms of cancer and is showing a rapid increase in incidence and yet exhibits poor survival rates. Compared to many other common cancers, the molecular changes that occur in this disease are relatively poorly understood. However, genes encoding chromatin remodeling enzymes are frequently mutated in OAC. This is consistent with the emerging concept that cancer cells exhibit reprogramming of their chromatin environment which leads to subsequent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
94
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(103 citation statements)
references
References 43 publications
9
94
0
Order By: Relevance
“…Gene dysregulation is a hallmark of cancers . An open chromatin profile study revealed that there are substantial changes in the regulatory chromatin environment in the cancer cells and uncovered an important role for ETS and AP1 TFs in driving the changes in gene expression found in oesophageal adenocarcinoma cells . In this cfDNA study, we also demonstrate that the chromatin openness state of EC patients differs from that of healthy people.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Gene dysregulation is a hallmark of cancers . An open chromatin profile study revealed that there are substantial changes in the regulatory chromatin environment in the cancer cells and uncovered an important role for ETS and AP1 TFs in driving the changes in gene expression found in oesophageal adenocarcinoma cells . In this cfDNA study, we also demonstrate that the chromatin openness state of EC patients differs from that of healthy people.…”
Section: Discussionmentioning
confidence: 52%
“…For this reason, the length of cancer patient cfDNA is shorter than that of healthy people. Other study also revealed that the chromatin state is more open in esophagus cancer cell lines than in normal cell lines …”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations